Тwo Metonymies of Serbian Material Culture in Translation - Daničić, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Over the past decades, metonymy has evolved from a poetic device to a conceptual system grounded in human experience. The aim of the paper is to investigate translation strategies which may be applied to the translation of popular Serbian cultural metonymies into English. The translation-related analysis focuses on the degree of translation equivalence achieved when a culture-specific term is conveyed into the target culture, or the extent of its adaptation when direct equivalence is lacking.The two analyzed examples (Serbian: rakija, pogača) are taken from the domain of gastronomy, one of the striking epitomes of material culture. The findings of the research show that there is no universal translation “recipe” which may be applied in the process of metonymy translation, and that in translation practice, metonymy translation is largely context-based.
Keywords: translation studies; metonymy; culture-specific items; translation equivalence; domestication; foreignization